2009
DOI: 10.1111/j.1365-2796.2008.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variation on chromosome 9p21.3 and arterial stiffness

Abstract: Objective. Genome wide association studies have consistently reported associations between a region on chromosome 9p21.3 and a broad range of vascular diseases such as coronary artery disease (CAD), aortic and intracranial aneurysms and type-2 diabetes (T2D). However, clear associations with intermediate phenotypes have not been described so far. To shed light on a possible influence of this chromosomal region on arterial wall integrity, we analyzed associations between single nucleotide polymorphisms (SNPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
6
36
1
Order By: Relevance
“…are of importance. 8 We have previously reported an association of aneurysm-associated genetic variations on chromosome 9p21.3 with reduced abdominal aortic stiffness, 26 while this study showed higher stiffness in carriers of the D allele. Deranged abdominal aortic stiffness indicates impaired integrity of the aortic wall which might be important in aneurysmal disease.…”
Section: Multiple Regression Analysescontrasting
confidence: 49%
“…are of importance. 8 We have previously reported an association of aneurysm-associated genetic variations on chromosome 9p21.3 with reduced abdominal aortic stiffness, 26 while this study showed higher stiffness in carriers of the D allele. Deranged abdominal aortic stiffness indicates impaired integrity of the aortic wall which might be important in aneurysmal disease.…”
Section: Multiple Regression Analysescontrasting
confidence: 49%
“…However, the mechanisms by which these alleles affect the incidence of CAD remain to be elucidated (Shen et al, 2008b;Ding et al, 2009;Scheffold et al, 2011). Some authors have suggested that these polymorphisms may impair the mechanical properties of the arterial wall and thus influence vascular diseases (Bjorck et al, 2009). In our study, rs10757274G was not significantly associated with CAD in the population we selected (P = 0.08); this observation may be related to sample size and individual susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathophysiological links between the genetic and physiological components remain largely unknown [26,33,34]. In addition, some studies have reported that SNPs can affect arterial stiffness [8]; examples include SNPs in genes such as those encoding the renin-angiotensin-aldosterone system, matrix protein/metalloproteinases, the nitric oxide pathway, b-adrenergic/endothelin receptors, the inflammatory cascade, and others [35][36][37][38][39].…”
Section: Biological Consideration: Explanation For the Genes Andmentioning
confidence: 99%